2021
DOI: 10.1051/0004-6361/202141009
|View full text |Cite
|
Sign up to set email alerts
|

The long period of3He-rich solar energetic particles measured by Solar Orbiter 2020 November 17–23

Abstract: We report observations of a relatively long period of 3 He-rich solar energetic particles (SEPs) measured by Solar Orbiter. The period consists of several well-resolved ion injections. The high-resolution STEREO-A imaging observations reveal that the injections coincide with extreme ultraviolet jets and brightenings near the east limb, not far from the nominal magnetic connection of Solar Orbiter. The jets originated in two adjacent, large, and complex active regions, as observed by the Solar Dynamics Observat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…The median 3 He/ 4 He abundance ratio is greater than 0.1 for all spacecraft at both energies. Additionally, the 3 He/ 4 He abundance ratio at high energies is consistently larger than at low energies, consistent with previous studies (e.g., Mason 2007;Nitta et al 2015;Bučík et al 2018aBučík et al , 2021Mason et al 2021). The range of the 3 He/ 4 He ratios varies from 0.009 ± 0.001 to 41.3 ± 6.9, the latter event being observed by ACE on 2000 January 6 and whose calculated 3 He/ 4 He agrees with that obtained by Mason et al (2000).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The median 3 He/ 4 He abundance ratio is greater than 0.1 for all spacecraft at both energies. Additionally, the 3 He/ 4 He abundance ratio at high energies is consistently larger than at low energies, consistent with previous studies (e.g., Mason 2007;Nitta et al 2015;Bučík et al 2018aBučík et al , 2021Mason et al 2021). The range of the 3 He/ 4 He ratios varies from 0.009 ± 0.001 to 41.3 ± 6.9, the latter event being observed by ACE on 2000 January 6 and whose calculated 3 He/ 4 He agrees with that obtained by Mason et al (2000).…”
Section: Resultssupporting
confidence: 90%
“…This work serves to introduce a live catalog of 3 He-rich time periods using multiple spacecraft and covering multiple solar cycles. The release of this catalog is timely with the recent launches of two new missions active in the inner heliosphere that are capable of observing 3 He enhancements, namely Parker Solar Probe (Wiedenbeck et al 2020) and Solar Orbiter (Bučík et al 2021;Mason et al 2021). The catalog will be continuously updated, and major updates will be properly documented and reported in separate publications.…”
Section: Discussionmentioning
confidence: 99%
“…New space missions at a close distance from the Sun, Parker Solar Probe, and Solar Orbiter may bring new insights on the role of EUV waves in ISEP events (see Wiedenbeck et al, 2020;Cohen et al, 2021;Mason et al, 2021;Bučík et al, 2021, for the first reported ISEP events from these missions). For instance, measurements made close to the source of ISEP events remove uncertainties due to interplanetary transport effects.…”
Section: Discussionmentioning
confidence: 99%
“…None of them report recurrent ion injection. [42] report a configuration with two large and complex nearby active regions which may have been responsible for five recurrent particle injections observed by EPD between 17 and 20 November 2020. All of them showed enhanced 3 He/ 4 He and Fe/O abundance ratios and several of them concurrent electron injections.…”
Section: He-rich Eventsmentioning
confidence: 98%
“…All of them showed enhanced 3 He/ 4 He and Fe/O abundance ratios and several of them concurrent electron injections. [42] conjecture that there may be a long-lived interaction between the negative polarity of one active region and the positive polarity of the neighboring active region, leading to the magnetic reconnection which drives the acceleration of ions and electrons. The two active regions were also located such that they produced a longitudinally extended source (∼ 40 • ) which may explain the multiple injections from the same source region.…”
Section: He-rich Eventsmentioning
confidence: 99%